Pendampingan Inovasi Dan Diversifikasi Produk Berbasis Kebutuhan Pasar Bagi UMKM Kota Cirebon - Khaerul Anam; Rudi Kurniawan; Nurul Fathonah; Pratama Putra Sanjaya (CV. Multi Kreasi Media, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth and employment generation in Indonesia. However, many MSMEs, particularly in the food and culinary sector, continue to face challenges such as limited product variety, low utilization of digital technologies, and insufficient understanding of market needs. This Community Service Program aimed to enhance the capacity of MSMEs in product innovation and market-oriented product diversification in Cirebon City. The program employed a participatory approach consisting of five stages: partner needs assessment, market needs survey, product innovation workshops, product development mentoring, and evaluation. The participating MSMEs included Dana Kinasih, Syukuri, Torani Sumoer Makmur, Sambal Anakku, and Rumah Kukus. The results demonstrated significant improvements in both innovation capacity and business competitiveness. The total number of products increased from 8 to 16, average monthly revenue rose from IDR 3,000,000 to IDR 4,500,000, and the number of new customers increased by 25%. Furthermore, pre-test and post-test evaluations indicated substantial improvements in participants’ understanding of product innovation, digital marketing, e-commerce, and the application of Artificial Intelligence (AI) in business. Market survey findings revealed that consumers preferred products with modern packaging (85%), diverse flavor variants (70%), and convenient online purchasing options (75%). These findings suggest that market-oriented product innovation and diversification mentoring is an effective approach to improving the competitiveness and sustainability of MSMEs in Cirebon City.